Network security know it all - Joshi, James B. D. (Burlington, MA, USA : Morgan Kaufmann, 2008)
Network Security: Know It All explains the basics, describes the protocols, and discusses advanced topics, by the best and brightest experts in the field of network security. Assembled from the works of leading researchers and practitioners, this best-of-the-best collection of chapters on network security and survivability is a valuable and handy resource. It consolidates content from the fields leading experts while creating a one-stop-shopping opportunity for readers to access the information only otherwise available from disparate sources. * Chapters contributed by recognized experts in the field cover theory and practice of network security technology, allowing the reader to develop a new level of knowledge and technical expertise. * Up-to-date coverage of network security issues facilitates learning and lets the reader remain current and fully informed from multiple viewpoints. * Presents methods of analysis and problem-solving techniques, enhancing the readers grasp of the material and ability to implement practical solutions. * Examples illustrate core security concepts for enhanced comprehension.
Ch 1 Network Security Overview-- reprint Ch 8 from Peterson/Davie, Computer Networks 4e (2007) -- 45pp -- Ch 2 Network Attacks-- by Joshi-- reprinted from Qian, Information Assurance (2007)-- 20 pp -- Ch 3 Security and Privacy Architecture-- reprint Ch 9 from McCabe, Network Analysis, Archit. & Design/3e (2007)-- 20 pp -- Ch 4 Concepts in IP Security-- reprint Ch 14 from Farrel, Internet Protocols (2004)-- 40 pp -- Ch 5 Security in Wireless Systems-- reprint Ch 13 from Garg, Wireless Communication & Networking (2007)-- 35pp -- Ch 6 Mobile Security and Privacy-- reprint Ch 9 from Zheng, Smart Phone & Next Gen Mobile Computing (2006) -- 70 pp -- Ch 7 Network Security Algorithms- reprint Ch 17 from Varghese, Network Algorithmics (2005)-- 15 pp -- Ch 8 Optical Network Survivability-- reprint Ch 10 from Ramaswami, Optical Networks/2e (2002)-- 50 pp -- Ch 9 Secure and Resiliant Routing-- by Medhi, reprinted from Qian, Information Assurance (2007)-- 40 pp -- Ch 10 Practical IPv6 Security Solutions-- reprint Ch 23 from Loshin, IPv6 2e (2004)-- 45pp.
Includes bibliographical references and index.
Keywords: Computer networks -- Security measures; Electronic books